2016
DOI: 10.1039/c5ra22790a
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative optimization and assessments of supplemented tea polyphenols in dry dog food considering palatability, levels of serum oxidative stress biomarkers and fecal pathogenic bacteria

Abstract: The objective of this study was to investigate the effects of supplementation of tea polyphenols (TP) in dry dog food on the palatability of dry dog food, serum oxidative stress biomarkers, and fecal pathogenic bacteria in adult dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…Strickling et al (2000) evaluated the palatability of canine meal containing 5 g/kg of commercial oligosaccharide, and also observed no rejection or preference for the samples. Chen et al (2016) developed canine meal rich in antioxidants containing up to 1% tea extract. The dogs preferred the samples with up to 0.5%, demonstrating they Research, Society andDevelopment, v. 10, n. 2, e57510212987, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i2.12987 may perceive the changes in flavor, with a consequent change in their consumption pattern.…”
Section: Resultsmentioning
confidence: 99%
“…Strickling et al (2000) evaluated the palatability of canine meal containing 5 g/kg of commercial oligosaccharide, and also observed no rejection or preference for the samples. Chen et al (2016) developed canine meal rich in antioxidants containing up to 1% tea extract. The dogs preferred the samples with up to 0.5%, demonstrating they Research, Society andDevelopment, v. 10, n. 2, e57510212987, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i2.12987 may perceive the changes in flavor, with a consequent change in their consumption pattern.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, higher TPC, TFC, and antioxidant capacity of dog foods were recorded following the addition of fermented medicinal plants, which indicates the retention of plant metabolites (polyphenols) in the foods. Chen et al [40] also reported the retention of tea polyphenols in dry dog foods. In a previous study, when glasswort was added at 2% to pork patties, antioxidant capacities were also increased [41].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have been conducted to investigate dog food preference. It is noteworthy that food preference is one of the most important parameters to assess food acceptance among animals because the higher the food preference, the easier and more enjoyable is the administration of bioactive substances [40]. Intake ratios are the best indicators of overall food preference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The products had thus a different attractiveness to the dogs and the food attractiveness is in accordance with the food intake ratio, but without the intake ratios data, it remains unclear how the products attractiveness would have impacted the overall dogs' food preference. Consequently, one may infer that measuring only one of these two parameters during a two‐bowl consumption test is not adequate to explain food preference (Chen et al, ; Dust et al, ). Indeed, the conclusions on the factors that govern the food preference may depend on the concordance between the intake ratios and the first choices.…”
Section: Discussionmentioning
confidence: 99%